Targeted metabolomic profiling of total fatty acids in human plasma by liquid chromatography-tandem mass spectrometry - Aidaros, Anas Al; Sharma, Charu; Langhans, Claus-Dieter; Okun, Jürgen G.; Hoffmann, Georg F.; Dasouki, Majed; Chakraborty, Pranesh; Aljasmi, Fatma; Al-Dirbashi, Osama Y. (Metabolites, 2020)
This article reports a targeted metabolomic method for total plasma fatty acids (FAs) of clinical or nutritional relevance. Thirty-six saturated, unsaturated, or branched-chain FAs with a chain length of C8-C28 were quantified using reversed-phase liquid chromatography-tandem mass spectrometry. FAs in plasma (10 μL) were acid-hydrolyzed, extracted, and derivatized with DAABD-AE (4-[2-(N,N-Dimethylamino)ethylaminosulfonyl]-7-(2-aminoethylamino)-2,1,3-benzoxadiazole) at 60 °C for 1 h. Derivatization resulted in a staggering nine orders of magnitude higher sensitivity compared to underivatized analytes. FAs were measured by multiple-reaction monitoring using stable isotope internal standards. With physiological and pathological analyte levels in mind, linearity was established using spiked plasma. Intra-day (n = 15) and inter-day (n = 20) imprecisions expressed as variation coefficient were ≤10.2% with recovery ranging between 94.5–106.4%. Limits of detection and limit of quantitation ranged between 4.2–14.0 and 15.1–51.3 pmol per injection, respectively. Age-stratified reference intervals were established in four categories: <1 month, 1–12 month, 1–18 year, and >18 year. This method was assessed using samples from patients with disorders affecting FAs metabolism. For the first time, C28:0 and C28:0/C22:0 ratio were evaluated as novel disease biomarkers. This method can potentially be utilized in diagnosing patients with inborn errors of metabolism, chronic disease risk estimation, or nutritional applications.
Gesehen am 25.11.2020